Low-dimensional catalysts for oxygen reduction reaction - Tong, Xin; Zhan, Xinxing; Rawach, Diane; Chen, Zhangsen; Zhang, Gaixia; Sun, Shuhui (Progress in natural science, 2020)
Developing highly efficient electrocatalysts to facilitate the sluggish cathodic oxygen reduction reaction (ORR) is a key challenge for high-performance fuel cells. Low-dimensional materials have attracted great attention recently because of their unique structure and properties. In this review, the application of zero-dimensional (0D), one‐dimensional (1D), and two‐dimensional (2D) materials in ORR are discussed and particular attention is given to the relationship between their structure and the ORR activity. Graphene-based materials, transition metal dichalcogenides, transition metal oxide, nanotubes, nanoribbons, nanowires, and single-atom ORR catalysts are introduced and classified by their geometric dimension. [Display omitted] •Recent progress on low-dimensional catalysts for ORR are systematically summarized.•The electronic structure of low-dimensional catalysts affects the ORR activity.•The active sites of each low-dimensional catalysts are discussed.